EU Regulation of Fast Fashion Advertising: A Tobacco Analogy? - Korchahin, Dmytro (Teisė, 2025)
The article deals with the justification of the adopting of advertising legal requirements for the fast fashion sector in the EU. In light of this objective, it seeks to elaborate on similarities between the fast fashion and the tobacco industries. The article proposes imposing regulatory measures for fast fashion advertising, similar to those applied to tobacco advertising in the European Union (EU), or even going beyond that. Thus, taking into account the similarities between these sectors, it proposes either to adapt tobacco-related advertising regulations to the regulation of the fast fashion sector (specifically for the area of advertising of fast fashion) in the EU (e.g., partial prohibitions on some domains, warnings, etc.) or to consider a complete advertising ban on fast fashion advertising in the EU.